Bush studies - Baynton, Barbara, 1857-1929.; Garner, Helen, 1942- (Melbourne : Text Publishing, 2012)
"No one ever wrote about the bush like Barbara Baynton. In the half-dozen stories in this book she conjures a nightmarish world for the women who live in it, a place of danger, lonliness and horror. Stark and searing, Bush studies is unforgettable, one of the most original books in Australian literature."--Back cover.
Dreamer -- Squeaker's mate -- Scrammy 'and -- Billy Skywonkie -- Bush church -- Chosen vessel.
Keywords: Baynton, Barbara, -- 1857-1929.; Frontier and pioneer life -- Australia -- Fiction; Women -- Australia -- History -- 19th century -- Fiction; Short stories, Australian; Women authors, Australian -- Biography; Australia -- Social conditions -- Fiction; Australian